GASTROINTESTINAL HELMINTHIASIS IN GUINEA PIG (CAVIA PORCELLUS) FAMILY-COMMERCIAL BREEDING FARMS IN ANCASH, PERU - García J., Cristina (2013)
The objective of this study was to determine the prevalence, identification and quantification of helminths present in guinea pigs (Cavia porcellus) in the finishing phase from family-commercial breeding farms in the district of Caraz, Ancash, Peru. The stomach, small intestine and large intestine of 100 animals were collected and all parasites were identified and counted. The prevalence of gastrointestinal nematodes was 89%. Identified parasites were Paraspidodera uncinata, Trichuris spp, Capillaria spp and Trichostrongylus colubriformis showing prevalence of 83, 31, 18 and 2% respectively and without differences due to sex. The frequency of monoparasitism, biparasitism and triparasitism was 49, 35 and 5% respectively.